Targeting of CAT and VCAM1 as Novel Therapeutic Targets for DMD Cardiomyopathy - Li, Bin; Xiong, Weiyao; Liang, Wen-Miin; Chiou, Jian-Shiun; Lin, Ying-Ju; Chang, Alex C. Y. (Frontiers in Cell and Developmental Biology, 2021)
Duchenne muscular dystrophy related cardiomyopathy is the leading cause of early mortality in DMD patients. There is an urgent need to gain a better understanding of the disease molecular pathogenesis and develop effective therapies to prevent the onset of heart failure. In the present study, we used DMD human induced pluripotent stem cells (DMD-hiPSCs) derived cardiomyocytes (CMs) as a platform to explore the active compounds in commonly used Chinese herbal medicine (CHM) herbs. Single CHM herb (DaH, ZK and CQZ) reduced cell beating rate, decreased cellular ROS accumulation, and improved structure of DMD hiPSC-CMs. Cross-comparison of transcriptomic profiling data and active compound library identified nine active chemicals targeting ROS neutralizing Catalase (CAT) and structural protein Vascular Cell Adhesion Protein 1 (VCAM1). Treatment with Quecetin, Kaempferol and Vitamin C, targeting CAT, confered ROS protection and improved contraction; treatment with Hesperidin and Allicin, targeting VCAM1, induced structure enhancement via induction of focal adhesion. Lastly, overexpression of CAT or VCAM1 in DMD hiPSC-CMs reconstituted efficacious effects and confered increase in cardiomyocyte function. Together, our results provide a new insight in treating DMD cardiomyopathy via targeting of CAT and VCAM1, and serves as an example of translating Bed to Bench back to Bed using a muti-omics approach.